Food riddles in Tuvan and Russian linguocultures - Chesnokova, Olga S.; Usmanov, Timur F. (The New Research of Tuva, 2022)
The article presents a contrastive linguistic and culturological analysis of the game description of food and ingredients in the riddles of two folklore traditions related to the Turkic (Tuvan) and Slavic (Russian) linguocultures. The subject of the article is riddles about food, its object is linguistic means that create images of food in the riddles of Tuvan and Russian ethnic communities. The research is based on about 300 Tuvan and Russian food riddles taken from Tuvan and Russian folklore publications.They classify the content and poetics of Tuvan and Russian riddles about food depending on objective natural and geographical conditions, specialties of national cuisines and the dominant ideas of the national worldviews, as well as typological features of languages. In order to interpret the strategies for the presentation of food in riddles, we applied the theoretical ideas of Gennady P. Melnikov’s system linguistics.The article examines and compares descriptions of similar food ingredients according to the criteria of imagery and national markedness in Tuvan and Russian riddles: about salt, tea, wild plants, nuts, onions, tawny daylilies, dairy products, eggs, meat products and alcohol. It has been confirmed that the semantic scheme of typical Tuvan phrases features the characteristic determinant of the Turkic languages in the texts of food riddles, while the semantic scheme of Russian riddles shows the event-related determinant of inflectional languages, including Russian.
Keywords: folklore; riddle; Tuvans; Russians; food; poetics; dialogue of cultures; Tuvan folklore